Proceedings of the 4th World Congress on Integrated Computational Materials Engineering (ICME 2017) - Mason, Paul; Fisher, Charles R.; Glamm, Ryan; Manuel, Michele V.; Schmitz, Georg J.; Singh, Amarendra K.; Strachan, Alejandro (The Minerals, Metals & Materials Series, 2017)
This book represents a collection of papers presented at the 4th World Congress on Integrated Computational Materials Engineering (ICME 2017), a specialty conference organized by The Minerals, Metals & Materials Society (TMS). The contributions offer topics relevant to the global advancement of ICME as an engineering discipline. Topics covered include the following: ICME Success Stories and Applications Verification, Validation, Uncertainty Quantification Issues and Gap Analysis Integration Framework and Usage Additive Manufacturing Phase Field Modeling Microstructure Evolution ICME Design Tools and Application Mechanical Performance Using Multi-Scale Modeling.